MiRNAs in β-Cell Development, Identity, and Disease - Martinez-Sanchez, Aida; Rutter, Guy A.; Latreille, Mathieu (Frontiers in Genetics, 2017)
Pancreatic β-cells regulate glucose metabolism by secreting insulin, which in turn stimulates the utilization or storage of the sugar by peripheral tissues. Insulin insufficiency and a prolonged period of insulin resistance are usually the core components of type 2 diabetes (T2D). Although decreased insulin levels in T2D have long been attributed to a decrease in β-cell function and/or mass, this model has recently been refined with the recognition that a loss of β-cell “identity” and dedifferentiation also contribute to the decline in insulin production. MicroRNAs (miRNAs) are key regulatory molecules that display tissue-specific expression patterns and maintain the differentiated state of somatic cells. During the past few years, great strides have been made in understanding how miRNA circuits impact β-cell identity. Here, we review current knowledge on the role of miRNAs in regulating the acquisition of the β-cell fate during development and in maintaining mature β-cell identity and function during stress situations such as obesity, pregnancy, aging or diabetes. We also discuss how miRNA function could be harnessed to improve our ability to generate β-cells for replacement therapy for T2D.